THE INFLUENCE OF MICROBIAL PERSISTENCE OF DENTAL PLAQUE ON THE PATHOGENESIS AND COURSE OF GENERALIZED PERIODONTITIS - Andrii Ye. Demkovych; Yuliia I. Poliukhovych; Petrо A. Hasiuk; Аnna Z. Мykolenko; Anna B. Vorobets; Eduard V. Beliaiev (Клінічна та профілактична медицина)
Introduction. In the pathogenesis of chronic inflammation of periodontum, dental plaque penetrates to the bottom of the gingival sulcus and enters the connective tissue interstitium under the epithelium, causing inflammation.